Identificação da região da saglin que interage com o domínio-A da proteína Thrombospondin Related Anonymous Protein (TRAP) e caracterização da interação entre TRAP e saglin em Anopheles spp - Degelo, Giovana Caramaschi [UNESP] (2015)
Salivary!gland!invasion!by!sporozoites!of!Plasmodium!genus!is!a!crucial!step! to! life! cycle! in! mosquitoes! of! Anopheles! genus, and! an! obligate! step! to! malaria! transmission! occurs.! TRAP! A! domain,! a! sporozoite! protein! that! is! secreted! on! anterior! tip! of! parasite! upon! contact! with! salivary! glands,! interacts! with! saglin,! a! major!gland!protein.!This!interaction!is!fundamental!to!gland!invasion.!This!process! occurs! in! Anopheles0 gambiae! infected! with! Plasmodium0 berghei! or! Plasmodium0 falciparum.!In!Brazil,!Anopheles0darlingi!is!the!main!vector!of!malaria!parasite.!Near! 80%! of!malaria! cases! are! due! Plasmodium0vivax,! annually,! and! about! 20%! due! to! Plasmodium0falciparum.! In! previous! studies! of! our! lab,! it!was! observed! 80%! of! P.! falciparum! infection! in! An.0 darlingi! collected! in! Rondonia,! Porto! Velho.! This! probably!happens!because!An.0darlingi!can!be!easily!infected!with!P.0falciparum,!but! can!not!efficiently!transmit!them.!We!compare!An.0gambiae!saglin!sequence!with0An.0 darlingi0sequences,!and!SG1!and!SG1B!were!the!most!related!sequences,!with!27%! of!similarity.!Brazilian!P.0falciparum!isolated!were!sequenced,!and!key!amino!acids! related!to!salivary!gland!invasion,!are!preserved.!We!characterize!for!the!first!time,! An.0gambiae! saglin! region! responsible! to! interact!with! A!domain!of!TRAP,! and!we! observed!that!these!sequences!have!no!homology!with!An.0darling!ones.!An.gambiae...